2020
DOI: 10.1016/j.molcel.2020.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Transcriptional Activation by Hepatic Reprogramming Factors

Abstract: Highlights d Foxa proteins and Hnf4a sequentially and cooperatively bind to chromatin in cells d Foxa3 transfers from the distal to proximal regions of transcription start sites d Foxa3 physically and functionally interacts with RNA polymerase II d Foxa3 travels together with RNA polymerase II to induce liver gene expression

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 59 publications
4
35
0
Order By: Relevance
“…Repression of neural stemness by these factors is achieved by binding to genes whose expression is enriched in embryonic neural cells, repressing transcription of neural enriched genes. Meanwhile, they activate genes that confer the property of non-neural cells, for example, the activation of liver-specific genes by FOXA3 (Horisawa et al, 2020) and activation of epithelial gene CDH1 by HHEX in the present study. Functioning as both a transcriptional repressor and an activator might be a general feature of prodifferentiation transcription factors (Abate-Shen et al, 2008;Gaston et al, 2016).…”
Section: Discussionsupporting
confidence: 52%
“…Repression of neural stemness by these factors is achieved by binding to genes whose expression is enriched in embryonic neural cells, repressing transcription of neural enriched genes. Meanwhile, they activate genes that confer the property of non-neural cells, for example, the activation of liver-specific genes by FOXA3 (Horisawa et al, 2020) and activation of epithelial gene CDH1 by HHEX in the present study. Functioning as both a transcriptional repressor and an activator might be a general feature of prodifferentiation transcription factors (Abate-Shen et al, 2008;Gaston et al, 2016).…”
Section: Discussionsupporting
confidence: 52%
“…For instance, SOX8 is reported to play a role in embryonic development, but also participates in neuronal cell fate determination in a transient and time-dependent manner [ 31 ]. Additionally, transcription factors in this category included those with a role in non-neuronal/endothelial cell phenotypes, for example FOXA3 with a role in establishing hepatic cell fate and ETV1, which is reported to participate in the establishment of His–Purkinje system development [ 32 , 33 ]. This category also included genes for factors that function as repressors of other transcription factors, or partner with some factors that are required for maintaining pluripotency.…”
Section: Resultsmentioning
confidence: 99%
“…Successful reprogramming of embryonic or adult fibroblasts has been reported by the co-overexpression of FoxA3, GATA4, and HNF1α [4] or HNF4α, together with either FoxA isoform [5] or HNF1β with FoxA3 [6]. Studies on the abovetype of "induced-Hepatocytes" (iHep cells) have demonstrated the need for co-operation between these factors to induce hepatic targets [7].…”
Section: Liver Developmentmentioning
confidence: 99%